Context-Aware Wireless-Based Cross-Domain Gesture Recognition - Kang, Hua; Zhang, Qian; Huang, Qianyi (IEEE internet of things journal, 2021)
Recently, significant efforts have been made to enable WiFi-based gesture recognition. However, models trained with data collected from specific domain suffer from significant performance degradation when applied in a new domain. In practice, various WiFi sensing techniques have provided us with a full knowledge of domain information including discrete variables, i.e., environment and subject, as well as continuous variables, i.e., location and orientation. Previous works haven't fully explored these domain information or need to integrate substantial links' information to use them. Intuitively, we can boost gesture recognition accuracy by accounting for all these domain information with different properties. We propose a new framework not being restricted to link number which combines an adversarial learning scheme with feature disentanglement modules. They together conduct two-stage alignment between each of the source domains and the target domain to eliminate all gesture irrespective information. We also present an attention scheme based on discriminative information of each source and target domain to promote positive transfer from source to target domain. Our model is evaluated on the Widar 3.0 data set and achieves an improvement of 3%-12.7% in cross-domain average accuracy, demonstrating the superiority.